Caracterização das áreas verdes no perímetro urbano de Marechal Cândido Rondon-PR - Wild, Gabriela de Bona (2018)
The inclusion of green areas provides spaces that contribute to the improvement of the life of the population and become a means of interaction of human activities with the environment. Squares and parks are elements within the urban space, when wellstructured serves the population and helps combat the degradation, besides to support the recovery, protection and conservation of environmental patrimony. In this context the objective of this research were to characterize the Green Areas in the urban space of Marechal Cândido Rondon county. In order to do so, an analysis was made of the evolution of the urban space in relation to green areas from 1960 to 2017, as well as locating, quantifying and qualifying these areas for the purpose of calculating the Index of Green Areas (IGA). In order to know how the municipality is managing these areas and to have an equilibrium between quality, quantity and distribution. This tripod provides indicators that influence the performance of green areas. The quality is aimed at meeting the concepts of green areas (Cavalheiro et al., 1999), the quantity is related to IGA (Nucci, 2001) and distribution must meet the scope range according to the defined category (Fontes and Shimbo, 2006). After this analysis it was noticed the need for improvements in the existing green areas. With this diagnosis, proposals were made to use the areas of environmental protection by raising the minimum quantity per inhabitant and the insertion of new squares within the scope range in the urban space. The research also proposed the creation of a linear park in order to contribute to environmental quality and create a new leisure option for the population